INDONESIAN ENGLISH LECTURERS’ VIEWS ON WORLD ENGLISHES IN ENGLISH LANGUAGE TEACHING: A QUALITATIVE INQUIRY - Rasyid Fahmi Suroso (ETERNAL (English Teaching Journal), 2022)
This study investigates English lecturers’ view on World Englishes in English Language Teaching (ELT). For this purpose, three English lecturers from a private university in Sleman were interviewed. The results revealed the divergence in acknowledging and applying World Englishes (ie. Non-native varieties of English) in the classroom. The finding of this study showed five major themes: (a) English as a communication tool, (b) Experience in communicating with native speakers (and/or non-native speakers), (c) The uniqueness of the use of World Englishes, (d) English teaching method applied by lecturers, (e) World Englishes, Global Englishes, and other relevant aspects to discuss.